Constable and Toop - Jones, Gareth P. (Amulet Books, 2013)
Something mysterious and terrible is happening throughout Victorian London: Ghosts are disappearing. When this reaches the attention of the Ghost Bureau, the diligent but clueless Mr. Lapsewood, a paranormal paper-pusher, is sent to investigate, and what he discovers is grave. The Black Rot has arrived—a voracious spiritual infestation whereby empty haunted houses suck in unsuspecting ghosts and imprison them. Lapsewood’s investigation weaves through the plotlines of several other memorable characters—both living and dead—including an undertaker’s son who can see ghosts, a serial throat-slasher reminiscent of Jack the Ripper, an evangelical exorcist, and many more. The living and dead must work together if they hope to destroy the Black Rot—before it destroys both the ghost and human worlds.